SUKAF Bandar Puncak Alam 2024: community rallies for health and wellbeing - Md Nadzir, Noor Khairul; Ab Fatah, Hanis Syazwani; Muzaini, Kamarulzaman; Yaacob, Siti Sara; Xin Wee, Chen (Faculty of Medicine, 2025)
On Saturday morning, October 12, 2024, hundreds of residents gathered for the much-anticipated Karnival Sukan Antara Fasa (SUKAF) Carnival, a day-long event focused on health, fitness, and community bonding at IJM Land Central Park, Bandar Puncak Alam, Selangor. Organized by the local council in collaboration with the Public Health Medicine Department, Faculty of Medicine and Hospital Al-Sultan Abdullah (HASA), UiTM the carnival offered various activities to promote healthier lifestyles.